Thermoelectric current in a graphene Cooper pair splitter - Z. B. Tan (Nature Portfolio, 2021)
Thermoelectricity due to the interplay of the nonlocal Cooper pair splitting and the elastic co-tunneling in normal metal-superconductor-normal metal structure is predicted. Here, the authors observe the non-local Seebeck effect in a graphene-based Cooper pair splitting device.